Social Media Growth Blueprint for Plastic Surgeons: Insights and Considerations From Personal Experience - Ahmad Saadya, MBBCh, MRCS (Eng); Tarek El-Tantawy, MBBCh, MRCS, FRCS (Plast) (Plastic and Reconstructive Surgery, Global Open)
Background:. Social media platforms such as TikTok have recently emerged as influential tools for information dissemination, offering plastic surgeons new opportunities to promote their practices. However, these platforms also present significant challenges regarding online safety, ethical considerations, and the potential spread of misinformation. Methods:. This study analyzes the experience of gaining 100,000 followers on TikTok within 6 months, highlighting the excitement of rapid growth alongside the challenges posed by the potential for misinformation. We propose a strategic approach to leveraging social media effectively and ethically, focusing on storytelling, educational content, and audience engagement; highlighting unique selling propositions; utilizing analytics; and maintaining consistency. Ethical considerations in medical communication are also discussed, emphasizing the need for robust guidelines. Results:. From December 2023 to June 2024, the author posted 56 videos in Arabic, the target market’s language. These videos garnered 16,566,900 views and 758,500 likes, with an average video length of 95.36 seconds. This growth led to a 47% increase in nonsurgical aesthetic consultations. Engagement and educational content, such as study tips, received the highest views, totaling 5.6 million, demonstrating the importance of such content in building a follower base for targeted marketing. Conclusions:. Our findings highlight the power and potential risks of social media in healthcare, advocating for a balanced approach that maximizes benefits while mitigating the spread of misinformation.